NEURAL NETWORK SYSTEM FOR SELECTION OF TABLE TENNIS EQUIPMENT - Валерій Абударович Тазетдінов; Світлана Володимирівна Сисоєнко (Вісник Черкаського державного технологічного університету, 2021)
The article examines the optimization of search processes and the relevance of the use of artificial neural networks for the selection of table tennis equipment. With the help of neural networks, it is possible to solve any task. The problem is only to make the right choice of architecture and structure of the neural network, the algorithm of its operation and to formalize the source data, the result and the corresponding transformation. The problem of clustering the table tennis equipment market is considered. The result of the research has become the creation of information-analytical system "Neuro TT" for the analysis of the table tennis equipment market and the possibility of selecting the optimal combination of rubbers and blade. The structure of such a neural network system has been developed. It consists of three information banks, which contain information about the properties of rubbers and blades, as well as known combinations of rubbers and blades. The use of such a system will allow to forecast the development trends of the table tennis equipment market, manufacturers to plan and change the structure of production, buyers (players) and sellers to fully meet the information needs.